The logarithmic form of the equation y=loga x is equivalent to the exponential form x=ay. To rewrite one form in the other, keep the base the same, and switch sides with the other two values.
X=numerator
y=denominator
the sum of numerator and denominator=x+y
we suggest this system of equations:
y=x-3
(x+5) / (y+5)=5/6
we solve this system of equation by substitution method.
(x+5) / (x-3+5)=5/6
(x+5) / (x+2)=5/6
6(x+5)=5(x+2)
6x+30=5x+10
6x-5x=10-30
x=-20
y=x-3=-20-3=-23
Teh sum of the numerator an denominator=-20+(-23)=-43
Answer: -43
Answer:
9
Step-by-step explanation:
Given
p(x) = 5x² - 3x + 7 ← substitute x = 1
p(1) = 5(1)² - 3(1) + 7 = 5(1) - 3(1) + 7 = 5 - 3 + 7 = 9
2/x ^6-3 you do the opposite of everything